Adapting at multiple scales: Towards a contextualised adaptive reuse of disused commercial infrastructure in secondary South African cities - Madolo, Bongane (School of Architecture, Planning and Geomatics, 2018)
In the early 1990s about 50 000 m² of office space was developed in the Central Business District (CBD) of Nelspruit for the Mpumalanga Provincial Government. The office space was spread out in a number of office buildings around the CBD. Between 2003-and 2005 the Provincial Government moved out of these office buildings to an office complex on the outskirts of the CBD, as a result a portion of the CBD was left vacant. The commercial sector has not really recovered since then and the CBD is beginning to experience urban decay. With this as background the dissertation, explores regeneration of a CBD and the opportunities that lie in large scale disused concrete frame buildings in Nelspruit, a secondary South African city. Affordable housing plays an important role in the development of the project, not only because it addresses a practical need for housing in the city, but also because it starts to speak to transformation of a city that largely remains anti-poor. The exploration in-to timber construction plays an equally important role in addressing questions of making buildings differently, looking at regional industry and craft, and the use of more sustainable building material. Research in to this topic was primarily aided by a 4-week research trip to Mezimbite Forest Centre in Beira, Mozambique. The objective is not to create a blueprint on which all the buildings are to be adapted because each existing building by virtue of its context alone, is unique and has challenges that are specific to it that need to be addressed. The objective is to develop a different way of adapting large scale buildings. One that breaks the monolith, makes connections and through its material is rooted in its broader context. Ideas that are tested in 32 Bell Street, a nine-storey building in the CBD of Nelspruit. Johannesburg's regeneration is looked at as an example of regeneration because it is the best example of a South African city that has used the decline of its commercial office sector to bring about transformation to a CBD, with housing being an important part of that transformation. Johannesburg also offers some of the clues on what needs to evolve in the way office buildings are being adapted.